Determinants of Business Sustainability in MSMEs: A Systematic Literature Review - Mirza Esvanti; Sudarmiatin; Agus Hermawan (Abadi Institute, 2026)
An increasingly dynamic and competitive business environment in the digital era compels Micro, Small, and Medium Enterprises (MSMEs) to develop adaptive strategies and capabilities to maintain their sustainability. However, many MSMEs still face challenges in integrating internal resources and external opportunities to achieve long-term resilience. Therefore, this study aims to systematically identify and synthesize the key determinants influencing MSME business sustainability, focusing on managerial, technological, and relational capabilities, as well as relevant external conditions. The research employs a Systematic Literature Review (SLR) approach following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, analyzing publications indexed in the Scopus database from 2015 to 2025. The findings reveal that Knowledge Management Capability, Relational Capability, Digital Transformation, and Organizational Agility are critical internal factors enhancing innovation, operational efficiency, and business resilience. Meanwhile, external factors such as government policy support and strategic collaboration significantly strengthen MSME sustainability. The study concludes that integrating internal capabilities with external support creates a synergistic framework that is essential for ensuring the long-term success and competitiveness of MSMEs in a rapidly evolving business landscape.